The modern approach of the quasi-judge in his book (Fath Al-Ghaffar to the provisions of the Sunnah of our chosen Prophet) - Al - Matari, Mohamed Ahmed Mohamed Morshed (Journal of Humanities & Social Sciences, 2017)
This research dealt with the Hadithi approach of the judge Al Rubaie in his book (Fatah Al Ghafar Al Gamae Liahkam Sunat Nabeeina Al Mukhtar), where Al Rubaie was one of the most prominent scholars of the thirteenth century AH in Yemen, and he was a defender of the Sunah of the Messenger of Allah peace be upon him and his family, and this book is considered to be the latest literature in the Ahaadeeth of provisions, and the most comprehensive book in this field according to my limited knowledge; the book included the writings of the previous Scholars and added a lot, with a clarification of the ranks of these Ahadeeths and showing the strange ones in a nutshell. This research also deals with the introduction about judge Al Rubaie and his scientific position, and then the definition of his book, Fatih al-Ghaffar, and its importance, and his Hadithee approach in his book "Fateh al-Ghaffar" like his approach in finding the source of the Hadeeths and judging them, his approach in criticizing and modifying, and his approach in strengthening the weak Ahaadeeths and explaining the reasons behind that.
Keywords: Al-Rabai' approach; Fath Al-Ghaffar; Al-Jami; Sunnah rulings